PENGARUH PUPUK KANDANG AYAM DAN NPK SEBAGAI PUPUK DASAR TERHADAP KESUBURAN TANAH DAN HASIL TANAMAN TOMAT PADA ULTISOL KAMBU - KHUSNUL KHOTIMAH; SAHTA GINTING; FRANSISCUS S REMBON; DARWIS DARWIS; SYAMSU ALAM; NAMRIAH NAMRIAH (Fakultas Pertanian Universitas Halu Oleo, 2023)
This study aims to determine the effect of chicken manure and NPK fertilizer as a basal fertilizer on Ultisol soil fertility and tomato plant yields and to find out the dose of chicken manure and NPK fertilizer as a basal fertilizer that affect both Ultisol soil fertility and tomato crop yields. This research was carried out at the Field Laboratory II of the Faculty of Agriculture and the Integrated Laboratory of Halu Oleo University, from March to June 2022. This study was conducted using a Randomized Block Design (RBD). The treatment tested was chicken manure and NPK fertilizer as a basal fertilizer consisting of 4 treatments, namely treatment without chicken manure (K0), chicken manure 200 g polybag-1 (K1), chicken manure 400 g polybag-1 (K2), chicken manure 600 g polybag-1 (K3). Each treatment was repeated by 3 tests, so there were 12 experimental units. The results showed that the application of chicken manure and NPK fertilizer as a basal fertilizer with various doses had an influence on soil fertility and tomato crop yields. In the K0 and K1 treatment, the fertility status was low, while the K2 and K3 treatment the fertility status increases to moderate, while the dose of chicken manure and NPK fertilizer as basal fertilizers that had higher on ultisol soil fertility and tomato plant yields, namely a dose of 600 g polybag-1 (K3) when compared to and a dose of 0 g polybag-1 (K0).